Research on Ultrasonic Treatment in the Field of Actual Excess Sludge Treatment. Issue 4 (February 2021) - Zhao, Wei; Zhan, Xianhui; Liu, Weilin; Wang, Shuang; Deng, Jiangyang; Wei, Daiyan; Sun, Meng
Abstract: It is generally known that that the carbon source is always insufficient in biological denitrification, and the excess sludge is difficult to dispose of in wastewater plants. This study explored the optimized ultrasonic treatment method for the excess sludge for denitrification of sewage. The response surface methodology of three factors and three levels was used to investigate the effects of ultrasound energy density, ultrasonic time and pH on cell-lysis rate, and the optimum process parameters for ultrasonic treatment for excess sludge were confirmed. The optimum cell-lysis rate was 33.891 ± 0.5% at the ultrasonic sound energy density was 2.0 W·mL −1, ultrasonic time was 40 min and pH was 7.0. The detection of the coliforms including E.coli before and after ultrasonic cracking showed that the ultrasonically cracked sludge could kill these pathogenic bacteria and achieve the effect of making the excess sludge harmless. The ultrasonic treatment experiments showed that ultrasonic treatment could inactivate these pathogenic bacteria (including E.coli ) and make the excess sludge harmless.